CO2 Methanation over Cobalt Nanoparticles Embedded in ZIF‐L–Derived Porous Carbon. Issue 5 (10th February 2023) - Gholampour, Nadia; Zhao, Yingrui; Devred, François; Sassoye, Capucine; Casale, Sandra; Debecker, Damien P.
Abstract: Catalytic hydrogenation of CO2 into CH4 is an effective method to convert waste CO2 and green hydrogen into clean fuel on a large scale. However, the viability of such process largely relies on the development of highly active heterogeneous catalysts. Here, a tailored methanation catalyst, Co nanoparticles immobilized into a highly porous N‐doped carbon matrix, is prepared by the carbonization of a cobalt‐based layered zeolitic imidazolate framework (ZIF−L) material under an argon atmosphere. This catalyst displays a specific activity of 22.3 molCH4 /gcat .min at 350 °C, significantly outperforming a similar catalyst derived from the more conventional ZIF‐67 (11.7 molCH4 /gcat .min). This is explained by the stabilization of small Co nanoparticles (∼20 nm) and by the presence of abundant medium‐strength basic sites related to the nitrogen doping in the catalyst prepared from ZIF−L. Notably, the new catalyst shows high stability; no deactivation is observed up to 60 hours on stream. Abstract : CO2 methanation over cobalt nanoparticles : The carbonization of ZIF−L led to cobalt nanoparticles embedded in a porous nitrogen‐doped carbon material. The catalyst showed high activity in the CO2 methanation reaction; this is explained by the stabilization of small Co nanoparticles and by the abundant N species that act as basic sites for CO2 adsorption.